1999
DOI: 10.1017/s1431927600017980
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Mechanical Specimen Preparation for Tem and Sem Applications

Abstract: The continued reduction in the size of critical features in integrated circuits has resulted in the need to develop rapid, site-specific, sectioning techniques to enable efficient physical characterization of the structures of interest. We have implemented a mechanical polishing approach to achieve this objective with the additional goals of maximizing the number of targeted sites in a sample that can be analyzed, and minimizing physically destructive procedures, such as ion beam exposure. Precision sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…A number of FIB studies were performed at a range of tilt angles and accelerating voltages, but were not deemed to be effective in reducing the amount of redeposition or ion damage. It has also been suggested that conventional argon ion milling at low energies with very shallow incidence angles is effective in removing damage layers (Li et al, 1999). However, such mills were not performed in this study.…”
Section: Feal-wc Compositementioning
confidence: 84%
“…A number of FIB studies were performed at a range of tilt angles and accelerating voltages, but were not deemed to be effective in reducing the amount of redeposition or ion damage. It has also been suggested that conventional argon ion milling at low energies with very shallow incidence angles is effective in removing damage layers (Li et al, 1999). However, such mills were not performed in this study.…”
Section: Feal-wc Compositementioning
confidence: 84%